1999
DOI: 10.1116/1.581645
|View full text |Cite
|
Sign up to set email alerts
|

Silicon etch rate enhancement by traces of metal

Abstract: We report the effect of nickel and tungsten contamination on the etch behavior of silicon. This is studied in a molecular beam setup, where silicon is etched by XeF 2 and Ar ϩ ions. The etch process is directly monitored by the SiF 4 reaction products which leave the surface. The effect of contamination appears very pronounced after the ion beam is switched off: it leads to a temporary enhancement of the spontaneous etch rate on a time scale of 500 s. With traces of contamination on the order of 0.01 ML, the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2000
2000
2018
2018

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…As dimensions of features are decreasing, wafer contamination becomes more and more persistent. The main form of contamination consists of traces of metal, sputtered from walls or electrodes, which are deposited on wafer surface [7]. Depending on the type of reactor and materials used for electrodes, traces of Ca, Fe, Zn, Cr, Mn, Ni, Cu, and K in the range from 0.01 to 0.4 ML may be found on the wafer after etching.…”
Section: Introductionmentioning
confidence: 99%
“…As dimensions of features are decreasing, wafer contamination becomes more and more persistent. The main form of contamination consists of traces of metal, sputtered from walls or electrodes, which are deposited on wafer surface [7]. Depending on the type of reactor and materials used for electrodes, traces of Ca, Fe, Zn, Cr, Mn, Ni, Cu, and K in the range from 0.01 to 0.4 ML may be found on the wafer after etching.…”
Section: Introductionmentioning
confidence: 99%
“…Relatively few studies have been performed on this topic. It was shown that copper, deposited on the silicon wafer, increased the etch rate by factors up to two in fluorine containing plasmas (6)(7)(8). A second group of investigations concentrated on the effect of the mask material on the silicon etching characteristics of fluorine containing plasmas (9,10).…”
Section: Introductionmentioning
confidence: 99%